2004
DOI: 10.1097/01.asn.0000130082.67775.60
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset of Treatment with a Chemokine Receptor CCR1 Antagonist Prevents Progression of Lupus Nephritis in MRL-Fas(lpr) Mice

Abstract: Abstract. Slowly progressive renal injury is the major cause for ESRD. The model of progressive immune complex glomerulonephritis in autoimmune MRL lpr/lpr mice was used to evaluate whether chemokine receptor CCR1 blockade late in the disease course can affect progression to renal failure. Mice were treated with subcutaneous injections of either vehicle or BX471, a nonpeptide CCR1 antagonist, three times a week from week 20 to 24 of age. BX471 improved blood urea nitrogen levels (BX471, 35.1 Ϯ 5.3; vehicle, 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 32 publications
9
80
1
1
Order By: Relevance
“…Interestingly, CCR1, a receptor that can interact with both CCL3 and CCL9, was up-regulated only in established disease. This is consistent with studies showing that CCR1 is involved mainly in interstitial infiltration that occurs in the later stages of disease (29).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, CCR1, a receptor that can interact with both CCL3 and CCL9, was up-regulated only in established disease. This is consistent with studies showing that CCR1 is involved mainly in interstitial infiltration that occurs in the later stages of disease (29).…”
Section: Discussionsupporting
confidence: 81%
“…For example, treatment with oral fingolimod (FTY720) and with the targeted murine C3 complement inhibitor CR2-Crry was found to be more effective in ameliorating glomerular injury than in controlling interstitial infiltrates and lesions (37,38). Otherwise, blockade of CCR1 could selectively halt interstitial leukocyte recruitment and fibrosis but not glomerular injury in MRL/lpr mice (39). Some published studies demonstrated that CD4ϩ T cells were major infiltrating cells in glomeruli, whereas F4/80ϩ macrophages were predominant in the interstitium of both MRL/lpr mice and lupus-prone NZM2328 mice (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…63 For example, the chemokine CCL2 recruits CCR2 + proinflammatory macrophages and T cells into the glomerulus and the tubulointerstitium, 64,65 whereas CCR1 + cells only recruit to the interstitial compartment and not to the glomerulus in LN. 66 Other leukocyte subsets involve other chemokines and chemokine receptors for their recruitment into the kidney. 63,67 Leukocyte recruitment is tightly regulated.…”
Section: Intrarenal Pathogenic Mechanisms Of Lnmentioning
confidence: 99%